2018
DOI: 10.3390/molecules23082063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Volatile Organic Chemicals in Chrysanthemum indicum Linné on Blood Pressure and Electroencephalogram

Abstract: This study identified the volatile organic compounds in the essential oils that are extracted from Chrysanthemum indicum Linné (C. indicum Linné) and investigated the effects of the inhalation of these compounds. We detected a total of 41 volatile organic compounds, including 32 hydrocarbons, four acids, three alcohols, two ketones, and one aldehyde. In a sniffing test, seven types of volatile organic compounds were identified. Furthermore, the volatile organic compounds in C. indicum Linné that were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…The previously described reduced levels of SBP and DBP in the groups with PEO inhalation may be attributed to an improvement in leptin resistance and the reduced levels of total cholesterol and LDL cholesterol that consequently lowered the risk of cardiovascular diseases, with a hypotensive effect [ 31 , 41 ]. In the human clinical trial conducted by Kim et al [ 19 ], the inhalation of Chrysanthemum indicum L. odor led to reduced activity of sympathetic nerves but increased activity of parasympathetic nerves, which coincided with the results of reduced SBP and DBP levels.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The previously described reduced levels of SBP and DBP in the groups with PEO inhalation may be attributed to an improvement in leptin resistance and the reduced levels of total cholesterol and LDL cholesterol that consequently lowered the risk of cardiovascular diseases, with a hypotensive effect [ 31 , 41 ]. In the human clinical trial conducted by Kim et al [ 19 ], the inhalation of Chrysanthemum indicum L. odor led to reduced activity of sympathetic nerves but increased activity of parasympathetic nerves, which coincided with the results of reduced SBP and DBP levels.…”
Section: Resultsmentioning
confidence: 79%
“…The aromatic compounds in each sample were expressed in the relative ratio (%) of their respective peak area by converting the peak area to percentage based on the total peak area as 100%.The olfactory detector port (ODP) was used to examine the characteristics of each separated aromatic compound sensed by the human olfactory organ. Concertedly, the retention time and intensity of odor were measured and recorded using a sensor that divides the intensity into four levels [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, only frontal is detected in the present study [ 17 ]. In the case of mid beta wave of 15–20 Hz with high significance in active thinking and high alertness, Kim M. has shown that mid beta wave was increased during inhalation of (+)-α-pinene and terpinolene, which is correlated to decreased mid beta, indicating relaxation and reducing stress [ 15 , 18 ]. In addition, the effect of essential oil of Inula helenium root decreases the mid beta but only in the parietal region [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the present study showed an emotional state after inhalation of the undiluted oil, which happens in the same way as brain wave power. The visual analog score of orchid oil inhalation also showed higher scores in elegance and freshness [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Solid‐phase microextraction (SPME, Supelco Co., Bellafonte, PA, USA) was used to collect the volatile compounds of A. gigas Nakai upon roasting. Volatile compound extraction was adapted from Kim, Goo et al () with a slight modification. The sample, 3 g, and a magnetic bar were placed in a glass vial and tightly sealed with a silicon/teflon septum.…”
Section: Methodsmentioning
confidence: 99%